Analysis of Education and Health Quality of Children of TKW Families: A Case Study in Cianjur and Indramayu Regencies - Ferry Hadiyanto; Arsita Arsita; Rosleny Marliani (UIN Sunan Gunung Djati Bandung, 2017)
This study is aimed at aims knowing the education and health quality of children of TKW families in Sindanglaka Village, Karangtengah District of Cianjur Regency and Juntinyuat Village, Juntinyuat District of Indramayu Regency. By using survey data of 56 and 48 households in Cianjur and Indramayu Regencies respectively, data is processed using the probit model. The variables used in this research are children academic reports, frequency of children suffering from illness, education expenditure, health expenditures, children ages, education levels of heads of households, children dependence, and family responsibilities. The results show that education expenditure, children ages, and education levels of heads of households have a significant effect on children education, while children health is influenced by the ages of children and family responsibility.